Gilles Deleuze's Difference and Repetition: A Critical Introduction and Guide - Williams, James (Edinburgh Edinburgh University Press, 2003)
This is a revised, expanded and fully up-to-date critical introduction to Deleuze's most important work of philosophy. This is the first critical introduction to "Difference and Repetition" (first published in 1968): Gilles Deleuze's most important work of philosophy and one of the most significant texts of contemporary philosophy. By critically analysing of Deleuze's methods, principles and arguments, James Williams helps readers to engage with the revolutionary core of Deleuze's philosophy and take up positions for or against its most innovative and controversial ideas. The book will also help to extend Deleuze's work to philosophers working in the analytic tradition. New for this edition: significant new material on intensity, Deleuze and science and questions of action after Difference and Repetition, all of which feed into current debates about how Deleuzian philosophy relates to politics and ethics; guides students through the key debates and oppositions by engaging with latest interpretations of Deleuze by Levi Bryant, Anna Sauvagnargues, Daniel W. Smith, Henry Somers-Hall and Miguel de Beistegui; and, a final critical section introduces and gives brief descriptions of new works on Deleuze, contrasting the Williams reading with others.
Keywords: Deleuze, Gilles -- 1925-1995; 20th Century (1901-2000); Philosophy; France